Drug treatment of heart failure in the elderly - Berliner, D. (Herz, 2018)
The prevalence of heart failure increases with age. Changes in the age distribution and growing life expectancy will lead to a further rise. However, data concerning drug treatment of heart failure especially in the elderly are scarce. Subgroup analyses of the heart failure trials suggest that drug therapy in older patients should follow the recommendations in the current guidelines. In doing so, several common comorbidities in these patients (e. g., impaired renal function) have to be considered and may have an influence on the therapy (e. g., drug dose, choice of active pharmaceutical ingredient, etc.). Especially in old, multimorbid patients, possible interaction of drugs might play a substantial role. In many cases the main goal of the therapy, especially in the very elderly, is to improve symptoms and quality of life.